A Model Program for the Success of College Students with Attention and Learning Disorders - Demetriou, Cynthia; Miller, Gabrielle; Mason, Laurel G; Salvesen, Christine (Education Sciences & Society - Open Access, 2019)
Internationally, institutions of higher education have been called upon to engage college students with learning disabilities in campus life, to provide effective learning supports, and to hold high expectations (Tinto, 2012). Model programs providing comprehensive support to college students with learning disabilities are few and far between. As the number of college students needing learning support increases across many countries, there is a critical demand to identify programs and approaches that produce optimal outcomes for students. This article provides an overview of the legal structures on which supports for individuals with disabilities are based in the United States in comparison to Italy. For nearly forty years, a U.S. program called Strategic Alternative Learning Techniques (SALT) Center has extended federally mandated supports in to higher education. As Italy grows its tertiary programs and supports for students with learning disabilities, the SALT Center may serve as a helpful model program.